MORPHOLOGICAL, PHYSICAL AND CHEMICAL CHARACTERISTICS OF SOILS DERIVED FROM LIMESTONE ROCKS IN BARILI, CEBU - Enojada, Grace R.; Asio, Victor B. (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 18 No. 2, 2015, 2018)
Please see PDF file.